Common and rare variants in multifactorial susceptibility to common diseases. - Bodmer, W; Bonilla, C (2008)
Here, we give a historical overview of the search for genetic variants that influence the susceptibility of an individual to a chronic disease, from RA Fisher's seminal work to the current excitement of whole-genome association studies (WGAS). We then discuss the concepts behind the identification of common variants as disease causal factors and contrast them to the basic ideas that underlie the rare variant hypothesis. The identification of rare variants involves the careful selection of candidate genes to examine, the availability of highly efficient resequencing techniques and the appropriate assessment of the functional consequences of the implicated variant. We believe that this strategy can be successfully applied at present in order to unravel the contribution of rare variants to the multifactorial inheritance of common diseases, which could lead to the implementation of much needed preventative screening schemes.